(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The species composition and ecological state of the natural shrubland of the North-Western Black Sea Region is analyzed by the example of the territory of the south-steppe subzone of the Tiligul-Bug interfluves. The main floristic features of natural-shrub vegetation are highlighted in various typical habitats inherent in the dry steppe. It describes the main ecological and biotopical conditions of the shrubs vegetation growth within the study area. Almost all the natural vegetation of the remaining parts of the steppe landscape is preserved and investigated in the ravine biotopes, the locally ground, microclimatic and orographic specifics of which are decisive in terms of the formation and existence of their phytocoenoses. It is established that in the conditions of the transformed territory, natural shrub phytogroups combine components of different origins (steppe natives, introducents, invasive and adventitious species) that are almost identical in the biotopical relation to the primary-steppe shrubs. Their ecological, species and biotopical (gully-ravine) unification is visible in geobotanically and geographically different sub-zones of the steppe, differing only in terms of vegetation. Accordingly, the modern composition and structure of the shrub groups in the steppe-field territory does not show the expected tendency to «impoverish» and xerophytisation in the gradient of the southern vector. Also, under the condition of a sharp drop in marginal loading during the last 15 years, the natural shrub vegetation of the remaining parts of the steppe-balk terrain shows an accentuated tendency to expand the location of habitats. First and foremost, the expansion of squares of shrubbery is due to more moisturized microbodies with broken or turf worn down. At the same time, the species composition of shrub groups in the gullies of the geobotanically different areas remains practically unchanged, and only in talvegah forms mixed wood-shrub complexes based on local and invasive species.